Unpacking Resource Management and Parental Involvement at KB Alam Al-Fatah - Zahrah, Dieva Atikatuz; Fachmi, Alysia Zull; Destiandra, Sandra; Aisyi, Salwa Rahadatul; Ardini, Weldaviz Yulanda; Anggun, Sepenti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study examines how resource management evaluation and parental involvement contribute to the implementation of Early Childhood Education (ECE) at KB Alam Al-Fatah. Effective ECE management requires active collaboration between the institution and parents, as well as structured management of educators, facilities, funding, and stakeholder relationships. To obtain a comprehensive picture of the learning process, curriculum implementation, and interaction dynamics within the school environment, this research employs a qualitative methodology that includes documentation, semi-structured interviews, and non-participatory observation. The findings indicate that KB Alam Al-Fatah applies clear institutional management, proportional task distribution, responsive leadership, and the Merdeka Curriculum supported by a deep learning approach that emphasizes meaningful learning experiences. The availability of both indoor and outdoor learning materials (APE) also supports children’s holistic development. Parental involvement is reflected in regular communication, assistance with memorization activities, and participation in school programs. In summary, high-quality and holistic ECE services that meet children’s developmental needs can be achieved through integrated resource management and active parental engagement.